1999
DOI: 10.1046/j.1525-1438.1999.99052.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual outcomes following treatment for early stage gynecological cancer: a prospective multicenter study

Abstract: Data are presented of a prospective, longitudinal study on the impact of early stage gynecological cancer on sexuality. Women with a partner (n = 58) completed self-report questionnaires following diagnosis but prior to treatment and then at 6 and 12 months post-treatment. A single assessment was also obtained from a healthy comparison group (n = 103). Pre-treatment cancer patients reported fewer and less trouble with sexual problems compared to healthy controls. Neither sexual satisfaction nor sexual activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 16 publications
4
22
0
Order By: Relevance
“…There are five longitudinal studies on sexual rehabilitation conducted during the first year of posttreatment for early stage gynecological cancer (Andersen, Anderson, & deProsse, 1989;Kylstra et al, 1999;Lalos, Jacobsson, Lalos, & Stendahl, 1995;Schover, Fife, & Gershenson, 1989;Weijmar Schultz, van de Weil, & Bouma, 1991). Results are unequivocal: Researchers report a stable frequency of sexual activity and sexual satisfaction as well as a decline in frequency of sexual activity and sexual satisfaction, although all investigators mention sexual response disruption over time (see Table 1).…”
Section: Literaturementioning
confidence: 99%
“…There are five longitudinal studies on sexual rehabilitation conducted during the first year of posttreatment for early stage gynecological cancer (Andersen, Anderson, & deProsse, 1989;Kylstra et al, 1999;Lalos, Jacobsson, Lalos, & Stendahl, 1995;Schover, Fife, & Gershenson, 1989;Weijmar Schultz, van de Weil, & Bouma, 1991). Results are unequivocal: Researchers report a stable frequency of sexual activity and sexual satisfaction as well as a decline in frequency of sexual activity and sexual satisfaction, although all investigators mention sexual response disruption over time (see Table 1).…”
Section: Literaturementioning
confidence: 99%
“…Compared to a control group of women who received surgery for benign reasons, radical hysterectomy (i.e., surgical removal of the uterus, the parametria and uterosacral ligaments, the upper portion of the vagina, and the pelvic lymph nodes) in cervical cancer patients produced significantly more lubrication problems, a decrease in sexual activities, impairment in all phases of the sexual response cycle, and an increase in diagnosable sexual dysfunctions (Grumann, Robertson, Hacker, & Sommer, 2001;Kylstra et al, 1999). Certainly, the extent to which these findings are attributed to the diagnosis of cancer per se, as opposed to surgical factors, cannot be ruled out.…”
Section: Introductionmentioning
confidence: 99%
“…For example, research has shown that many people with cancer can experience an improved outlook on life, enhanced interpersonal 2 E. Gilbert et al 604 relationships (Andrykowski, Brady, & Hunt, 1993), as well as increased couple communication, mutual understanding (Kylstra et al, 1999;Manne et al, 2004) and improved relational and emotional closeness (Corney, Crowther, Everett, Howells, & Shepherd, 1993). In addition, a chronic illness such as cancer can potentially result in the construction of a number of new selves -selves that although altered by the cancer, are experienced as more fully realised than the pre-cancer self (Frank, 1993).…”
mentioning
confidence: 99%